Spread of a neurotropic murine coronavirus into the CNS via the trigeminal and olfactory nerves - Perlman, Stanley (Virology, 1989)
The route of entry into the central nervous system (CNS) of most neurotropic viruses has not been established. The coronavirus, mouse hepatitis virus strain JHM (MHV-JHM), causes acute encephalomyelitis and acute and chronic demyelinating diseases and is an important model system for virus-induced neurological disease. Suckling C578L/6 mice infected intranasally with MHV-JHM develop either the acute encephalomyelitis or a late onset, symptomatic demyelinating encephalomyelitis, depending on whether they are nursed by unimmunized or immunized dams. Analysis by in situ hybridization was used to determine the route of entry of MHV-JHM into the CNS in these mice. At early times, viral RNA was detected only in the trigeminal and olfactory nerves and in their immediate connections in all mice. A few days later, MHV-JHM RNA was found throughout the brain in mice dying of the acute encephalomyelitis, but remained confined to the entry sites in mice which did not develop acute disease. These results suggest that MHV-JHM enters the CNS via an interneuronal route in all mice, but that the presence of maternal antibody prevents the dissemination of virus via extracellular fluid. In addition, MHV-JHM may establish low-level persistence in the trigeminal or olfactory nerve or in one of its connections in mice that do not develop acute encephalomyelitis.